Wireless Data Communication Techniques to Coordinate Distributed Rooftop PVs in Unbalanced Three-phase Feeder - Rachmawati Rachmawati; Anita Fauziah; Nelly Safitri (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
A necessity of the availability of communication network to provide data transfer amongst the coordinated single-phase rooftop photovoltaic (PV) in unbalanced three-phase low voltage (LV) feeder is essential since fetching data within the sensor of each PV unit requires real-time measurement and reliable data exchange within smart grid (SG), loads and other PV units. The main objective of this paper is to model the popular Wi-Fi, WiMax and ZigBee wireless data communication techniques into algorithms using numerical analysis. Those communication technologies have low cost and low power consumption. The benefits and drawbacks of those considered wireless data communications are shown as the required data that transferred and appropriate coding is also proposed. The number of transmitted symbols and the processing time delay of the proposed data coding are numerically analyzed, the results indicated that the 100% penetration level of PV that resulted higher injected reactive power back into the networks is able to be overcome since the coordinated PVs along the feeder is communicating to lower the unbalanced voltage profile.